Perancangan Alat Inverator Energi Listrik Menggunakan Simulink Matlab - Balisranislam Balisranislam; Partaonan Harahap; Sudirman Lubis (Fakultas Teknik UMSU, 2021)
The need for electrical energy has become an inseparable part of people's daily lives in line with the increasing economy and development in the fields of technology, industry, information, research, agriculture and education. Electric motor machines containing coils of wire (inductors) where inductive loads absorb reactive power for magnetization needs, so the source (power plant) must supply greater power. Of course, this situation can cause voltage drops, increased current in the network and low power factor in the area near the load. Based on the simulation output, the resulting power factor has reached the standard (cos ) (SPLN T5.003-1, 2008) which is 0.85 lagging. However, in this study, the power factor is targeted to reach 0.9 lagging. Therefore, the researchers analyzed how much the capacitor bank needs to be added in order to achieve a power factor of 0.9 lagging.